MOTHER'S ACTORING IN CHILDREN'S CARE THROUGH RELIGIOUS LITERACY ACTIVITIES - Prawidya Lestari; Wahyu Bagas Rahino; Sukma Ayuningtiyas3 (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
Family is the main and first basis of education. Parents in the family are required to be able to carry out their role as good educators in the family. Education can be in the form of teaching, habituation, giving advice, setting an example, giving gifts and punishment. The purpose of this activity is assistance to mothers and families in raising children through religious literacy. Religious literacy uses Lukman's advice in QS. Lukman: 13-19. Lukman's advice contains educational values ​​and can be used as an Islamic family education curriculum. The research method for community service activities uses the Asset-based community development (ABCD) approach. The steps of the ABCD method start with preparation, implementation, reporting and presentation activities. The form of this activity is in the form of a Focus Group Discussion (FGD) with the women of Tepus Kulon Village. The results of the activity showed that the results of the FGD activities resulted in an increased understanding of the mother's role in raising children in the family and an understanding of Lukman's advice to his children. In addition, family understanding is the first environment that influences one's education and as the first and foremost vessel for personality development and growth has achieved a good initial understanding.